PENGEMBANGAN E-LEARNING DALAM PERSPEKTIF MAQ?SHID SYAR?’AH - Achmad Beadie Busyroel Basyar (Jurnal Penelitian Ilmiah INTAJ, 2020)
E-learning is one of much needed educational media. Especially since the Covid-19 pandemic occurred. Where education is carried out in online. Education needs to adapt to this new phenomenon. And one of the most powerful is the use of digital technology media for education. E-learning is education that is implemented using information and communication technology as a tool. However, the use of information technology in education needs to be done carefully, because if not, it will greatly affect the effectiveness of learning. That's why the development of e-learning requires principles to increase its effectiveness. On the other side, a development principle from a sharia perspective is also needed, to see the exact law, priority scale, and priority scale. This research is a descriptive qualitative research. This type of research is literature study. Where data sources are obtained from literature references, books, research reports, and others. Then processed critically to find the conclusion for the results. The results of this study can be formulated in two points. First, e-learning as a medium is wash?lah for education, where education is wash?lah for the protection of reason. Second, the principles of developing e-learning in the maq?shid of sharia are three things: 1) the principle of strengthening the objectives of sharia, 2) the principle of priority (pedagogy, objectives, media, and suitability), and 3) the principle of virtue.